2020
DOI: 10.1096/fj.201903244r
|View full text |Cite
|
Sign up to set email alerts
|

Hyodeoxycholic acid (HDCA) suppresses intestinal epithelial cell proliferation through FXR‐PI3K/AKT pathway, accompanied by alteration of bile acids metabolism profiles induced by gut bacteria

Abstract: Bile acids (BAs) have been implicated in regulation of intestinal epithelial signaling and function. This study aimed to investigate the effects of hyodeoxycholic acid (HDCA) on intestinal epithelial cell proliferation and explore the underlying mechanisms. IPEC‐J2 cells and weaned piglets were treated with HDCA and the contributions of cellular signaling pathways, BAs metabolism profiles and gut bacteria were assessed. In vitro, HDCA suppressed IPEC‐J2 proliferation via the BAs receptor FXR but not TGR5. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…In comparison with HFD group, the level of HDCA increased significantly and the β-MCA level decreased in HFD + AEE group. Previous study showed that HDCA altered BA metabolism profiles induced by gut bacteria ( Song et al, 2020 ). Meanwhile, it was found that HDCA was a candidate for anti-atherosclerotic drug therapy via increasing the ability of HDL ( Shih et al, 2013 ).…”
Section: Discussionmentioning
confidence: 96%
“…In comparison with HFD group, the level of HDCA increased significantly and the β-MCA level decreased in HFD + AEE group. Previous study showed that HDCA altered BA metabolism profiles induced by gut bacteria ( Song et al, 2020 ). Meanwhile, it was found that HDCA was a candidate for anti-atherosclerotic drug therapy via increasing the ability of HDL ( Shih et al, 2013 ).…”
Section: Discussionmentioning
confidence: 96%
“…In the ileum, we noted that an increase in the expression of ASBT and FXR after supplementing BA. Exogenous BA supplementation resulted in increases of several BA species, namely TUDCA, HDCA, and THDCA in the ileum, which can also function as a weak FXR agonist ( 58 ). However, the conflicting results of FXR induce ASBT expression in mice and inhibit ASBT expression in rabbits but do not affect ASBT in humans ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Formononetin (FMNT), a isoflavonoid, possesses anti-inflammatory, antioxidant, and antitumoral properties (44)(45)(46), and supplementation of isoflavonoids can reduce the incidence and mortality of cancers (47,48). Hyodeoxycholic acid (HDCA) can suppress intestinal epithelial cell proliferation through the FXR-PI3K/AKT pathway (49). The reduced levels of lysophosphatidylethanolamine (LPEs), key components of cellular membranes, can explain the rapid cellular proliferation of malignancies (50).…”
Section: Discussionmentioning
confidence: 99%